THE EFFECT OF RESPONSIBILITY, DISCIPLINE, PERFORMANCE, AND EMPLOYEE POLICY ON PARTICIPANT SERVICE SATISFACTION - Sawal Sartono; Mokhamad Eldon; Indra Hadi Rosyid Novela (Universitas Tulungagung, 2024)
With the rapid development of health services businesses, more and more public and private hospitals are offering health services. One form of service is providing drugs recommended by doctors. The existence of drug supplies in a hospital is very important because it is the main component in building a quality hospital. The problem formulation is: